2008
DOI: 10.1104/pp.108.116293
|View full text |Cite
|
Sign up to set email alerts
|

Role of Swollenin, an Expansin-Like Protein fromTrichoderma, in Plant Root Colonization  

Abstract: Swollenin, a protein first characterized in the saprophytic fungus Trichoderma reesei, contains an N-terminal carbohydratebinding module family 1 domain (CBD) with cellulose-binding function and a C-terminal expansin-like domain. This protein was identified by liquid chromatography-mass spectrometry among many other cellulolytic proteins secreted in the coculture hydroponics medium of cucumber (Cucumis sativus) seedlings and Trichoderma asperellum, a well-known biocontrol agent and inducer of plant defense res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
144
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(153 citation statements)
references
References 44 publications
2
144
1
6
Order By: Relevance
“…Likewise, a recent study found that overexpression of ''swollenin,'' a fungal protein with an expansin-like domain, enhanced benign colonization of cucumber roots by Trichoderma reesei (31). These reports, combined with our results, suggest that expansin-type modules have been adapted by diverse microbes to facilitate their interactions with plants, whether for benign colonization as in B. subtilis and T. reesei or for pathogenic attack as in C. michiganensis or the other plant pathogens noted above.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a recent study found that overexpression of ''swollenin,'' a fungal protein with an expansin-like domain, enhanced benign colonization of cucumber roots by Trichoderma reesei (31). These reports, combined with our results, suggest that expansin-type modules have been adapted by diverse microbes to facilitate their interactions with plants, whether for benign colonization as in B. subtilis and T. reesei or for pathogenic attack as in C. michiganensis or the other plant pathogens noted above.…”
Section: Discussionmentioning
confidence: 99%
“…In Trichoderma, adherence to the root surface can be mediated by hydrophobins, which are small hydrophobic proteins of the outermost cell wall layer that coat the fungal cell surface, and expansin-like proteins related to cell wall development. Trichoderma asperellum produces the class I hydrophobin TasHyd1, which has been shown to support the colonization of plant roots, possibly by enhancing its attachment to the root surface and protecting the hyphal tips from plant defence compounds (Viterbo & Chet, 2006), and the swollenin TasSwo, an expansin-like protein with a cellulose-binding domain able to recognize cellulose and modify the plant cell wall architecture, facilitating root colonization (Brotman et al, 2008). Plant cell-wall-degrading enzymes are also involved in active root colonization, as occurs with the endopolygalacturonase ThPG1 from Trichoderma harzianum (Morán-Diez et al, 2009).…”
Section: Trichoderma Spp Can Colonize Root Intercellular Spacesmentioning
confidence: 99%
“…These objectives are supported by a number of experimental data concerning the synergism with cellulases (Chen et al 2010;Kim et al 2009;Lee et al 2010;Quiroz-Castañeda et al 2011;Wang et al 2010Wang et al , 2011Zhou et al 2011). However, the biological role of expansin-type protein domains from microbes seems that of facilitating the interaction with plants, as colonization or symbiosis establishment (Brotman et al 2008;Dermatsev et al 2010;Kerff et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, expansin-like proteins have also been found in fungi and bacteria (often called swollenins or loosenins) (Bouzarelou et al 2008;Brotman et al 2008;Chen et al 2010;Dermatsev et al 2010;Kerff et al 2008;Lee et al 2010;Quiroz-Castañeda et al 2011;Saloheimo et al 2002;Yao et al 2008).…”
Section: Introductionmentioning
confidence: 99%